A DFT study of the acid–base properties of anatase TiO2 and tetragonal ZrO2 by adsorption of CO and CO2 probe molecules - Chen, Hsin-Yi Tiffany; Tosoni, Sergio; Pacchioni, Gianfranco (Surface science, 2016)
We have performed a comparative study of the acid–base characteristics of the surfaces of anatase TiO2 and tetragonal ZrO2. To this end we performed DFT+U calculations on CO and CO2 probe molecules adsorbed both on terraces and steps of the two oxides. For titania, CO adsorption results in a moderate adsorption energy (about −0.3eV) and in a positive shift of the CO stretching frequency (about +40cm−1), typical of Lewis acid sites, with no clear difference in the acidity between terraces or steps. For zirconia we found a similar CO binding energy as for titania, and a CO vibrational shift that depends on the location of the Zr cation: negligible on terraces, similar to TiO2 on steps. We conclude that the acidic properties are similar in the two oxide surfaces. Things are different for CO2 adsorption. On titania the interaction is weak and surface carbonates compete with physisorbed CO2, indicating a weak basic character. On the contrary, on zirconia three types of stable carbonates have been identified. Their vibrational frequencies are consistent with IR measurements reported in the literature. The most stable species forms on steps of the t-ZrO2 surface and consists of a CO32− unit which lies flat on the surface with the O atoms pointing towards three Zr ions. The species forms spontaneously by extraction of a lattice oxygen by an incoming CO2 molecule. The different reactivity points towards a much more pronounced basic character of zirconia compared to titania, at least if measured by CO2 adsorption. [Display omitted] •We performed a DFT study of the acid–base character of titania and zirconia surfaces.•We studied the adsorption of CO and CO2 as probe molecules for acidity and basicity.•CO is equally bound to flat and stepped TiO2 surfaces, but prefers steps on ZrO2.•CO2 is weakly bound to TiO2 and strongly bound to ZrO2, forming carbonates.•The two oxides exhibit comparable Lewis acidity, while ZrO2 is more basic.